Evaluation of the effectiveness of the Chronological Dental Mineralization Table of Permanent Teeth among Brazilians in the city of Belo Horizonte (Research, Society and Development, 2022)
The knowledge of an individual age, especially children and young people, is  important in civil and criminal cases, such as adoption and when is important determining criminal imputability. To estimate this age, when there are no suitable documents to prove it, body development factors are used, especially those that show the stages of mineralization of the teeth. To this estimation, numerous tables have been developed in the most diverse regions. The aim of this study was to analyze the accuracy of the Chronological Table of Mineralization of Permanent Teeth among Brazilians in a region different from that in which the method was developed, namely, Vale do Paraíba (SP - Brazil). For this purpose, 442 panoramic radiographs of individuals aged 5 years to 20 years and 4 months, taken in the central region of the city of Belo Horizonte (MG), were used. After applying the table, with the determination of the stages of each tooth present in the radiograph and an average between them, using the data developed by the authors, the total average percentage of correct answers was 63.5%, showing a low number, especially in the age range of 14 to 17 years. When the estimate was analyzed for sexual dimorphism, no significant differences were found. Through this study, one can perceive a need for standardization and detailing in the methodology, besides its updating and complementation with data that encompass dental development in the different regions of the country.